PENGAMBILAN MINYAK TERPENTIN DARI GETAH PINUS DENGAN METODE MICROWAFE ASSISTED HYDRO-DISTILATION (MAHD) - Sitti Humaerah; Ummu Kalsum; Ruslan Kalla (Ikatan Dosen Menulis, 2023)
Turpentine oil is the result of distillation of pine tree sap. The main content of turpentine oil is α-pinene which can be used for the synthesis of organic compounds such as paint and carbolic acid. This study aims to study the process of extracting turpentine oil using the Microwave Hydro-Distillation method. In this research studied the effect of time, power and volume of raw materials in the Microwave Hydro-Distillation process. The variables observed in this study were time (30, 40, 50, 60 and 70 minutes), power (150, 300 and 600 Watt) and raw material volume (150 ml). The quality of turpentine oil such as color, specific gravity, and refractive index were tested according to SNI 7633-2011, while the α-pinene content was analyzed using GC-MS. This study produced the highest yield of 28.22% in the extraction of raw materials of 150 mL using 300 and 600 Watts of power for 70 minutes with 85.01% α-pinene, 5.4% 3-carene and 2.27% β-pinene. Turpentine oil has a characteristic clear color from aquadest solvent with a refractive index of 1.465 and a specific gravity of 0.858 g/cm3, while from hexane solvent with a refractive index of 1.471 and a specific gravity of 0.863 g/cm3. The results of the study concluded that microwave energy has great potential to be used as an energy source for the process of extracting turpentine oil from pine resin because it can produce turpentine oil in a short time.